Living with the effects of cutaneous toxicities induced by treatment - Andreas Charalambous (Elsevier, 2017)
The introduction of targeted therapies in cancer treatment was accompanied with promising results including tumor control and patients survival benefits. However, these drugs just like their predecessors were associated with systemic side effects, including frequent and various cutaneous effects. Targeted therapies such as epidermal growth factor receptor, vascular endothelial growth factor receptor, kit, platelet-derived growth factor receptor, and BCR-ABL inhibitors as well as mammalian target of rapamycin inhibitors can induce cutaneous toxicities of varying severity. There are scarce studies on the actual impact of these toxicities on the patients' lives including the physical, social, and psychological aspects and overall quality of life. Patient's perspective in living with and beyond these toxicities remains largely uncharted but essential in optimizing care provided to those receiving treatment with targeted therapies.